Innate lymphocyte and dendritic cell cross‐talk: a key factor in the regulation of the immune response - Reschner, A.; Hubert, P.; Delvenne, P.; Boniver, J.; Jacobs, N. (Clinical and experimental immunology, 2008)
Summary Dendritic cells (DC) are specialized in the presentation of antigens and the initiation of specific immune responses. They have been involved recently in supporting innate immunity by interacting with various innate lymphocytes, such as natural killer (NK), NK T or T cell receptor (TCR)‐γδ cells. The functional links between innate lymphocytes and DC have been investigated widely and different studies demonstrated that reciprocal activations follow on from NK/DC interactions. The cross‐talk between innate cells and DC which leads to innate lymphocyte activation and DC maturation was found to be multi‐directional, involving not only cell–cell contacts but also soluble factors. The final outcome of these cellular interactions may have a dramatic impact on the quality and strength of the down‐stream immune responses, mainly in the context of early responses to tumour cells and infectious agents. Interestingly, DC, NK and TCR‐γδ cells also share similar functions, such as antigen uptake and presentation, as well as cytotoxic and tumoricidal activity. In addition, NK and NK T cells have the ability to kill DC. This review will focus upon the different aspects of the cross‐talk between DC and innate lymphocytes and its key role in all the steps of the immune response. These cellular interactions may be particularly critical in situations where immune surveillance requires efficient early innate responses.